Strengthening International Fiscal Governance to Combat Global Tax Avoidance: A Policy and Literature-Based Analysis - Muhammad Ishlah Idrus; Muhammad Ikram; Anastasia D'Ornay (Universitas Muhammadiyah Makassar, 2025)
Global tax avoidance continues to undermine national revenues and weaken the integrity of international tax systems, particularly as cross-border economic activities expand in the digital era. This study examines how international fiscal governance can serve as an effective framework for mitigating global tax avoidance by analyzing key policies, regulatory instruments, and multilateral initiatives. Using a descriptive and policy-oriented approach, this research synthesizes recent literature, institutional reports, and global regulatory developments to evaluate the effectiveness of mechanisms such as the OECD/G20 Base Erosion and Profit Shifting (BEPS) project, the Global Minimum Tax (Pillar Two), automatic exchange of information, and strengthened tax transparency standards. The study finds that while international cooperation has significantly improved policy alignment and reduced opportunities for profit shifting, substantial challenges remain, including uneven adoption across jurisdictions, capacity gaps in developing countries, regulatory loopholes, and geopolitical asymmetries in negotiations. The analysis also highlights the growing importance of digital taxation frameworks as multinational enterprises increasingly shift value creation to intangible assets. This paper argues that stronger institutional coordination, equitable policy adoption, capacity-building for emerging economies, and enhanced enforcement mechanisms are critical to advancing global tax fairness. The findings contribute to a deeper understanding of how international fiscal governance can shape more coherent and sustainable tax systems, offering policy recommendations to support future reforms and strengthen global tax compliance.